Answer:
f = 1, w = 4
Step-by-step explanation:
Given the 2 equations
5w = 23 - 3f → (1)
4f = 12 - 2w (add 2w to both sides )
2w + 4f = 12 ( subtract 4f from both sides )
2w = 12 - 4f → (2)
Multiplying (1) by 4 and (2) by - 3 and adding the result will eliminate f
20w = 92 - 12f → (3)
- 6w = - 36 + 12f → (4)
Add (3) and (4) term by term to eliminate f
14w = 56 ( divide both sides by 14 )
w = 4
Substitute w = 4 into either of the 2 equations and solve for f
Substituting into (1)
5(4) = 23 - 3f
20 = 23 - 3f ( subtract 23 from both sides )
- 3 = 3f ( divide both sides by - 3 )
1 = f
Step-by-step explanation:
s is inversely proportional to t
If s= 0.6 , t= 4
s=k/t
0.6= k/4
k=2.4
If s=12, then
t=k/s
t=2.4/12
t=0.05
Answer: True
Explanation: hope this help
Answer:2/16
Step-by-step explanation:
With the facts you got here, you can make the following equation:
x*(x+2)=24
x^2+2x=24
x^2+2x-24=0
Then you can use the following formula (which you might have seen before):
x = (-b +/- sqrt(b^2-4ac))/2a
where
ax^2+bx+c=0
(-2 +/- sqrt(4+96))/2
(-2 +/- 10)/2
x_1 = 4
x_2 = -6